Galactic synchrotron distribution derived from 152 HII region absorption features in the full GLEAM survey - Su, H.; Macquart, Jean-Pierre; Hurley-Walker, Natasha; McClure-Griffiths, N.; Jackson, Carole; Tingay, Steven; Tian, W.; Gaensler, B.; McKinley, B.; Kapínska, A.; Hindson, L.; Hancock, Paul; et al. (Oxford University Press, 2018)
We derive the synchrotron distribution in the Milky Way disc from H II region absorption observations over -40° < l < 40° at six frequencies of 76.2, 83.8, 91.5, 99.2, 106.9, and 114.6 MHz with the GaLactic and Extragalactic All-sky Murchison widefield array survey (GLEAM). We develop a new method of emissivity calculation by taking advantage of the Haslam et al. (1981) map and known spectral indices, which enable us to simultaneously derive the emissivity and the optical depth of H II regions at each frequency. We show our derived synchrotron emissivities based on 152 absorption features of H II regions using both the method previously adopted in the literature and our improved method. We derive the synchrotron emissivity from H II regions to the Galactic edge along the line of sight and, for the first time, derive the emissivity from H II regions to the Sun. These results provide direct information on the distribution of the Galactic magnetic field and cosmic ray electrons for future modelling.